Gemcitabine-loaded biocompatible nanocapsules for the effective treatment of human cancer. (February 2013) - Paolino, Donatella; Cosco, Donato; Celano, Marilena; Moretti, Sonia; Puxeddu, Efisio; Russo, Diego; Fresta, Massimo
Aim: To encapsulate the nucleoside gemcitabine (GEM) in novel PEGylated polymeric nanocapsules (NanoGEM).Materials & methods: The biological activity of NanoGEM was tested both in vitro and in vivo in comparison with the free drug. The NanoGEM was made of polylactic acid and allowed the entrapment of a great amount of GEM.Results & discussion: The NanoGEM showed mean sizes of approximately 200 nm, a polydispersity index of approximately 0.1 and a ζ-potential of -30 mV. It exerted a stronger, quicker effect on the reduction of HEK293 cell growth in vitro in comparison with free GEM and had an in vivo antitumoral effect on the proliferation of xenograft tumors at a drug dosage tenfold less than its saline solution. The employment of nanocapsules increased the plasmatic half-life of the drug and allowed a great accumulation of GEM inside the tumors.Conclusion: NanoGEM represents a promising new tool for the treatment of cancer. Original submitted 16 November 2011; Revised submitted 21 June 2012; Published online 24 October 2012